PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Iswara Putra, Bagus Asta; Kartika Dewi, A.A Sagung (E-Jurnal Manajemen, 2016)
The aim of this study was to examine the direct effect of job satisfaction and organizational commitment on organizational citizenship behavior. This research was conducted in LPD Desa Adat Kedonganan using all employees amounted to 49 people as respondent. Sampling technique used in this study are saturated sampling technique. Data collected through interviews and questionnaires. The data analysis technique used is multiple linear regression. This study found that job satisfaction has positive influence on organizational citizenship behavior. Organizational commitment has positive effect on organizational citizenship behavior. To improve organizational citizenship behavior, LPD Desa Adat Kedonganan are advised to increase job satisfaction, especially by gving promotion to the employees who have done a good job and demonstrated performance continues to increase each year. In addition, it is recommended to increase organizational commitment in a way to get closer to employees so that employees feel like family in LPD Desa Adat Kedonganan.
Keywords: Job satisfaction, organizational commitment, organizational citizenship behavior